A comparative study of walking‐induced dust resuspension using a consistent test mechanism. (9th April 2014) - Tian, Y.; Sul, K.; Qian, J.; Mondal, S.; Ferro, A. R.
Abstract: Human walking influences indoor air quality mainly by resuspending dust particles settled on the floor. This study characterized walking‐induced particle resuspension as a function of flooring type, relative humidity (RH), surface dust loading, and particle size using a consistent resuspension mechanism. Five types of flooring, including hardwood, vinyl, high‐density cut pile carpet, low‐density cut pile carpet, and high‐density loop carpet, were tested with two levels of RH (40% and 70%) and surface dust loading (2 and 8 g/m 2 ), respectively. Resuspension fraction r a (fraction of surface dust resuspended per step) for house dust was found to be varied from 10 −7 to 10 −4 (particle size: 0.4–10 µ m). Results showed that for particles at 0.4–3.0 µ m, the difference in resuspension fraction between carpets and hard floorings was not significant. For particles at 3.0–10.0 µ m, carpets exhibited higher resuspension fractions compared with hard floorings. Increased RH level enhanced resuspension on high‐density cut pile carpet, whereas the opposite effect was observed on hard floorings. Higher surface dust loading was associated with lower resuspension fractions on carpets, while on hard floorings the effect of surface dust loading varied with different RH levels.